State Law Mandates for Reporting of Healthcare-Associated Clostridium difficile Infections in Hospitals - Reagan, Julie (Infect Control Hosp Epidemiol, 2015)
US state and territorial laws were reviewed to identify Clostridium difficile infection reporting mandates. Twenty states require reporting either under state law or by incorporating federal Centers for Medicare & Medicaid Services' reporting requirements. Although state law mandates are more common, the incorporation of federal reporting requirements has been increasing.